2015
DOI: 10.1002/adsc.201500160
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Chiral Indolines using an Imine Reductase from Paenibacillus lactis

Abstract: An enzymatic process for the efficient asymmetric reduction of 3H‐indoles as well as 3H‐indole iodides was developed for the first time. Using a new imine reductase identified from Paenibacillus lactis (PlSIR), various chiral indolines were facilely synthesized in good yields and excellent enantiopurities (up to >99% ee) under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 50 publications
3
49
0
1
Order By: Relevance
“…We modelled the active centre by using 1-methylnicotinamide( hydride donor), with substrate and one explicit water molecule in ad ielectric environment( Supporting Information). [10,20] According to our calculations, the energy barriers for our selected ketonesa re higher than for iminium ions of the chosen models ubstrates, but lower than for imine compounds ( Table 2). These differences in reactivity are supported by recent studies by the groups of Turner and Xu, who investigated reductiono fi minium salts and found faster conversion of iminium ions in comparison with the corresponding imines.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…We modelled the active centre by using 1-methylnicotinamide( hydride donor), with substrate and one explicit water molecule in ad ielectric environment( Supporting Information). [10,20] According to our calculations, the energy barriers for our selected ketonesa re higher than for iminium ions of the chosen models ubstrates, but lower than for imine compounds ( Table 2). These differences in reactivity are supported by recent studies by the groups of Turner and Xu, who investigated reductiono fi minium salts and found faster conversion of iminium ions in comparison with the corresponding imines.…”
mentioning
confidence: 72%
“…Theoretically calculated activation energies encourage the speculation that imines are protonated prior to hydride transfer from NADPH. [10,20] Regarding speculations of the roles of amino acid residues for C=Np rotonation in IREDs, [11,25] there is some supporting evidenceb ased on mutations of putative catalytically important aspartic acid residues displaying reduced catalytic efficiencies over wild-type enzyme. This is in accordance with the work of Mayr and co-workers,w ho described the electrophilicity of benzaldehyde-derived iminium ions and their higherr eactivities compared to substituted imines.…”
mentioning
confidence: 99%
“…The number of biochemically characterized IREDs is growing rapidly, indicating a great interest in this recently identified protein family . However, the molecular basis for substrate specificity, stereoselectivity, and the catalytic mechanism remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…IRED activity was also found in a remote homologue from Pseudomonas putida KT2440 ( R ‐IRED‐ Pp ) with low sequence identity to the other IREDs. During the preparation of this manuscript, further enzymes were biochemically characterized to expand the scope of IREDs . Recently, the crystal structures of R ‐IRED‐ Sk (PDB entries 3ZHB, 3ZGY), S ‐IRED‐ Ss (PDB entry 4OQY), S ‐IRED‐Sa (PDB entry 4OQZ), S ‐IRED‐ Bc (PDB entries 4D3F, 4D3D), S ‐IRED‐ Nh (PDB entry 4D3S), and R ‐IRED‐ Pp (PDB entry 3L6D) have been solved .…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes allow two "types" of reactions: (i) the reduction of a cyclic imine to a cyclic sec-amine or (ii) the reductive amination of a ketone with a primary amine yielding a sec-amine, where a proof of concept (Huber et al, 2014;Scheller et al, 2015) and preparative applications were demonstrated very recently (Wetzl et al, 2016). In the previous years, several research groups discovered a large number of IREDs (Gand et al, 2014;Huber et al, 2014;Li et al, 2015;Man et al, 2015;Mitsukura et al, 2013Mitsukura et al, , 2011Mitsukura et al, , 2010Rodríguez-Mata et al, 2013;Scheller et al, 2015;Wetzl et al, 2015). In addition, an imine reductase engineering database with more than 1000 putative IREDs is established (Scheller et al, 2014).…”
Section: Introductionmentioning
confidence: 99%